A role for the Auxin Response Factors ARF6 and ARF8 homologs in petal spur elongation and nectary maturation in Aquilegia. Issue 5 (14th June 2020) - Zhang, Rui; Min, Ya; Holappa, Lynn D.; Walcher‐Chevillet, Cristina L.; Duan, Xiaoshan; Donaldson, Emily; Kong, Hongzhi; Kramer, Elena M.
Summary: The petal spur of the basal eudicot Aquilegia is a key innovation associated with the adaptive radiation of the genus. Previous studies have shown that diversification of Aquilegia spur length can be predominantly attributed to variation in cell elongation. However, the genetic pathways that control the development of petal spurs are still being investigated. Here, we focus on a pair of closely related homologs of the AUXIN RESPONSE FACTOR family, AqARF6 and AqARF8, to explore their roles in Aquileiga coerulea petal spur development. Expression analyses of the two genes show that they are broadly expressed in vegetative and floral organs, but have relatively higher expression in petal spurs, particularly at later stages. Knockdown of the two AqARF6 and AqARF8 transcripts using virus‐induced gene silencing resulted in largely petal‐specific defects, including a significant reduction in spur length due to a decrease in cell elongation. These spurs also exhibited an absence of nectar production, which was correlated with downregulation of STYLISH homologs that have previously been shown to control nectary development. This study provides the first evidence of ARF6 / 8 homolog‐mediated petal development outside the core eudicots. The genes appear to be specifically required for cell elongation and nectary maturation in the Aquilegia petal spur.